Experiences of Thai-Muslim patients regarding inconsistent antiretroviral therapy adherence: An exploratory descriptive qualitative study - Pajongsil Perngmark; Oatcharaphon Sahawiriyasin; Eleanor Holroyd (Belitung Nursing Journal, 2023)
Background: Antiretroviral therapy (ART) has played a crucial role in saving countless lives of patients with HIV/AIDS across the world. However, despite its effectiveness, ART adherence still falls short globally, and non-adherence remains the primary cause of treatment failure. In the rural areas of southern Thailand, where the population is predominantly conservative Muslims, there has been an observed increase in ART non-adherence. Objective: This study aimed to explore experiences of inconsistent ART adherence among Thai-Muslim patients with HIV/AIDS (PWHAs) in southern Thailand. In addition, the perspectives of healthcare providers were also sought. Methods: Data were collected by conducting semi-structured in-depth interviews with ten Thai-Muslim PWHAs and five healthcare providers at a Voluntary Counseling-and-Testing Clinic. A content analysis approach was utilized to analyze the data. Results: Inconsistent ART adherence was reported. Religion/spiritual imperatives, forgetfulness, inadequate knowledge (of drug side effects and drug regime), misunderstandings (about being symptom-free and feeling well), boredom from long-term drug-taking regimes, as well as poor transportation and lack of family support (arising from non-disclosure of one’s HIV-serostatus due to HIV stigma) were emergent themes derived from the interviews with Thai-Muslim PWHAs. The healthcare providers’ interview data revealed their need for the integration of Islamic beliefs to provide better care. Conclusion: It is essential for healthcare teams to work collaboratively with patients’ religious beliefs to enhance ART adherence. Clinical nurses can contribute to the promotion of HIV-care services by integrating Islamic beliefs and Muslim culture into their practice, thus increasing patients' knowledge and motivation for ART adherence. This could entail utilizing Islamic prayer rituals as drug reminders, elaborating on Islamic moral beliefs concerning sickness and healing, and integrating the cultural imperatives of self-care in the Muslim community into ongoing care delivery. Cross-cultural nursing education and specialized training in HIV care should incorporate knowledge about Islamic and Muslim cultural beliefs.